2012
DOI: 10.1093/toxsci/kfs168
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Computational Modeling of Airflows and Vapor Dosimetry in the Respiratory Tracts of Rat, Monkey, and Human

Abstract: Computational fluid dynamics (CFD) models are useful for predicting site-specific dosimetry of airborne materials in the respiratory tract and elucidating the importance of species differences in anatomy, physiology, and breathing patterns. We improved the imaging and model development methods to the point where CFD models for the rat, monkey, and human now encompass airways from the nose or mouth to the lung. A total of 1272, 2172, and 135 pulmonary airways representing 17±7, 19±9, or 9±2 airway generations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(145 citation statements)
references
References 98 publications
3
138
0
Order By: Relevance
“…(59,(75)(76)(77)(78)(79) More recently, CFD applications have used surface models derived from imaging data from individual subjects. (80)(81)(82)(83) These models typically comprise the upper respiratory tract consisting of the oral airways, pharynx, and larynx, and upper lung airways from the trachea extending down through several generations of the lung. The limiting factor in determining how far down into the lung patientbased CFD models can go is driven by the resolution of the scanning procedure.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…(59,(75)(76)(77)(78)(79) More recently, CFD applications have used surface models derived from imaging data from individual subjects. (80)(81)(82)(83) These models typically comprise the upper respiratory tract consisting of the oral airways, pharynx, and larynx, and upper lung airways from the trachea extending down through several generations of the lung. The limiting factor in determining how far down into the lung patientbased CFD models can go is driven by the resolution of the scanning procedure.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
“…Another avenue that is receiving recent interest is the integration of distal lung mechanics through coupling of the 3D CFD model with 1D or 0D models at each outlet. (80,84,85) This should allow for a more realistic definition of airflow distribution at model outlets. DeBacker et al (86) showed good agreement between CFD predictions of airflow distribution and those derived from SPECT/CT by accounting for airway resistance.…”
Section: Fig 2 Coronal Slices Of 3d Single Photon Emissionmentioning
confidence: 99%
“…Hofmann (2011) reviewed the development of morphometric data for particle deposition modeling, including simulations of population variability from the data of Weibel (1963), Raabe et al (1976), and others. Currently, modelers have access to a substantial number of quantitative physiological and anatomical data sets (e.g., Asgharian et al, 2001Asgharian et al, , 2006Asgharian et al, , 2012Corley, Kabilan, & Kuprat, 2012;Newton, 1995, Chapter 5;Yeh & Schum, 1980). Also, medical scanning techniques are often used to define respiratory airways for aerosol deposition modeling Rostami, 2009).…”
Section: Respiratory Tract Anatomy and Physiologymentioning
confidence: 99%
“…Kimbell and colleagues were probably the first to mesh a three-dimensional respiratory tract structure used to model the gas flow (in the nose of the rat). Such models have been applied to upper, bronchial, and alveolar airways (Asgharian et al, 2012;Balásházy & Hofmann, 1993;Balásházy, Hofmann, Farkas, & Madas, 2008;Corley et al, 2012;Darquenne, Harrington, & Prisk, 2009;Ferron et al, 1991;Heistracher & Hofmann, 1995;Schroeter, Asgharian, Price, & McClellan, 2013;Zhang, Kleinstreuer, & Kim, 2009;). CFD models have proven useful for calculating detailed deposition patterns, but validation of the results are still under development (Hofmann, 2011;Oldham, Phalen, & Budiman, 2009;Rostami, 2009).…”
Section: Computational Fluid Dynamics Models Of Inhaled Particle Depomentioning
confidence: 99%
See 1 more Smart Citation